(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Criminal activities are on the rise globally, and they’re becoming a threat to the safety and security of residents in urban and rural areas. The use of closed-circuit television (CCTV) technology is an effective way of enhancing criminal investigation and preventing crime in public spaces. The barangay Mapulang Lupa has been experiencing an increase in criminal activities, prompting the need for the use of CCTV technology to monitor and deter criminal activities. This study aims to explore the potential of CCTV technology in enhancing criminal investigations in barangay Mapulang Lupa. The study findings revealed that the use of CCTV technology has a positive impact on enhancing criminal investigations in Barangay Mapulang Lupa. The majority of correspondents believed that the installation of CCTV systems led to a reduction in crime rates in the area. CCTV technology has also helped in identifying and prosecuting criminals of correspondents, indicating that the technology plays a significant role in criminal investigations. Additionally, CCTV has a deterrent effect on criminal activities of correspondents reporting a decrease in vandalism, theft, and other offenses in areas with CCTV cameras. Furthermore, the study findings showed that CCTV technology has helped to enhance public safety and reduce fear among residents. The study concludes that CCTV technology has significant potential to enhance criminal investigations in Barangay Mapulang Lupa. Technology has a positive impact on crime prevention, identification, and prosecution of criminals. CCTV technology has also been shown to have a deterrent effect on criminal activities, making public spaces safer for residents. The study recommends that the local government and law enforcement agencies continue to invest in CCTV systems and implement policies and procedures that maximize the effectiveness of this technology in crime prevention and investigation.